2021
DOI: 10.3390/molecules26123749
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Dynamical Evolution in Coum/SBE-β-CD Inclusion Complexes Revealed by Two-Dimensional FTIR Correlation Spectroscopy (2D-COS)

Abstract: A combination of Fourier transform infrared spectroscopy in attenuated total reflectance geometry (FTIR-ATR) and 2D correlation analysis (2D-COS) was applied here for the first time in order to investigate the temperature-dependent dynamical evolution occurring in a particular type of inclusion complex, based on sulfobutylether-β-cyclodextrin (SBE-β-CD) as hosting agent and Coumestrol (7,12-dihydorxcoumestane, Coum), a poorly-soluble active compound known for its anti-viral and anti-oxidant activity. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…This shift may be due to the formation of a-β-CD by hydrogen bonding between AEO and β-CD and the change in electron cloud density, resulting in the shift in the characteristic absorption peak frequency of the groups in a-β-CD; alternatively, it may be that the included guest is wrapped within the hydrophobic cavity of β-CD, and the original characteristic peak is covered by the characteristic peak of β-CD. The infrared absorption of a-β-CD is different from that of the physical mixture mainly at 1650 cm −1 and 1350 cm −1 , indicating the formation of a-β-CD [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…This shift may be due to the formation of a-β-CD by hydrogen bonding between AEO and β-CD and the change in electron cloud density, resulting in the shift in the characteristic absorption peak frequency of the groups in a-β-CD; alternatively, it may be that the included guest is wrapped within the hydrophobic cavity of β-CD, and the original characteristic peak is covered by the characteristic peak of β-CD. The infrared absorption of a-β-CD is different from that of the physical mixture mainly at 1650 cm −1 and 1350 cm −1 , indicating the formation of a-β-CD [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclodextrins (CDs) could be used to overcome this drawback. They are cyclic oligosaccharides that are able to complex apolar drugs and effectively improve their physicochemical properties, including water solubility [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and biological effects [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, authors demonstrated that anionic cyclodextrins (CDs), such as carboxymethyl-β-CD (CM-β-CD) and sulfobutylether-β-CD (SBE-β-CD), can electrostatically interact with CS to develop NPs for drug delivery [ 43 , 44 , 45 , 46 ]. Moreover, due to their hosting capacities, these CDs can include hydrophobic drugs [ 47 , 48 , 49 , 50 ], improving their physical–chemical properties (first of all, aqueous solubility). In this way, anionic CDs can act as gelling agents for CS, to prepare NPs, and in the meantime, they increase water solubility of lipophilic drugs, by complexation, permitting their encapsulation within CS NPs prepared in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%